How Metrics-Based Academic Evaluation Could Systematically Induce Academic Misconduct: A Case Study. Issue 2 (1st June 2018) - Han, Junhui; Li, Zhengfeng
Abstract: This article analyzes a case of postproduction misconduct, that is, the BioMed Central (BMC) retraction incident, which is the beginning of a series of massive retraction incidents that China has encountered in recent years. Our analysis echoes the pioneering research of STS scholar Mario Biagioli, who argues that our academic culture is shifting from "publish or perish" to "impact or perish." Getting a good score on the metrics of academic evaluation becomes the goal of some scholars, leading to the emergency of postproduction misconduct. As revealed in the BMC retraction incident, commercial agencies that claimed to be able to facilitate academic publishing manipulated the peer-review process of academic papers by fabricating their peer reviews to help some clinicians meet the requirements of the title assessment system. This article advances Biagioli's argument by expounding on the following two characteristics of the BMC retraction incident: first, peer reviews were fabricated by agencies instead of the authors themselves; second, the incident was induced systematically by the title assessment system, instead of particularly by individual factors of the authors. Through analyzing this case, we obtain important insight into postproduction misconduct, which is beneficial to more thoroughly understanding and then mitigating this new type of academic misconduct.